THE PROBLEM OF EXECUTION IN DISTRICT COURT AGAINST OVERLAPPING COURT DESCISION (A Study at the Cianjur District Court) - Bagus Mizan Albab; Abdul Rachmad Budiono; Sihabudin (CV. RADJA PUBLIKA, 2025)
Execution is a crown for a court especially for the head of district court to execute the court decision. In principle, execution does not need to be submitted through the district court if the losing party or defendant is willing to voluntary perform or fulfill the performance of the court decision (article 195 paragraph 1 HIR of article 206 paragraph 1 RBG). The petition of execution may only be filled against a court decision that meets the requirement for execution. In the practice law field, the problem with the implementation of execution of overlapping court decision with the similar or same object, same party, but have different court decisions. The research method used is normative juridical and the data used includes relevant legal regulation, court decisions and relevant legal literature. Therefore, towards this issue, this journal will discuss and convey solutions related to the issue of execution and its resolution strategy, with the aim that the court decision will be able to be executed (executable judgment).